Verification methods and algorithms of forces of the shock interactions in vibro-impact systems - Грабовский, Андрей Владимирович (Eastern-European Journal of Enterprise Technologies, 2010)
A new approach for determining the strength of shock interaction in vibro-impact systems. There are developed the criteria, algorithms, models for verification of these forces. There is resulted the example of the modelling problem decision.